2014
DOI: 10.1007/s11250-014-0605-6
|View full text |Cite
|
Sign up to set email alerts
|

Growth of sheep fed tannin-rich Albizia gummifera with or without polyethylene glycol

Abstract: Twenty-four intact male Bonga lambs were studied in a 100-day experiment to evaluate the effect of feeding tannin rich leaves of Albizia gummifera (AG) on nutrient utilization, growth performance, and carcass composition. The dietary treatments consisted of hay alone (T1, control), AG at 30 % of control diet + T1 (T2), and T2 + polyethylene glycol 6000 (PEG) (T3, 40 mg PEG, 1 kg AG/head on a dry mass (DM) basis. The lambs were individually fed at 50 g DM/kg live weight. In the last 10 days of the experiment, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The lower CPD both in sheep and in goats for non-PEG treatments might be associated with protein-binding effects of tannins. It has been reported that zebu cattle fed with dried leaves of several tanniferous trees and supplemented with PEG showed an increase of in vivo CP digestibility (Yisehak et al 2011 , 2014 ). Several authors have reported a reduction in protein digestibility in ruminants fed diets containing high levels of CTs.…”
Section: Discussionmentioning
confidence: 99%
“…The lower CPD both in sheep and in goats for non-PEG treatments might be associated with protein-binding effects of tannins. It has been reported that zebu cattle fed with dried leaves of several tanniferous trees and supplemented with PEG showed an increase of in vivo CP digestibility (Yisehak et al 2011 , 2014 ). Several authors have reported a reduction in protein digestibility in ruminants fed diets containing high levels of CTs.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 5 shows the reduction in rumen ammonia concentrations as related to CT concentration compared with CT-containing forages or non-CT-containing forages. Figure 5 implies that CT in forages significantly reduced rumen degradation of forage protein F I G U R E 2 Relationship between sheep and goats for ruminal dry matter (DM) digestibility (DMD) in response to feeding tannin-containing forages (Barry & Manley, 1984;Waghorn et al, 1987Waghorn et al, , 1990Waghorn, Douglas, Niezen, McNabb, & Foote, 1998;Waghorn, Tavendale, & Woodfield, 2002;Barahona, Lascano, Cochran, Morrill, & Titgemeyer, 1997;Woodward and Reed, 1997;Min et al, 2002aMin et al, ,b, 2012Bengaly et al, 2007;Yisehak et al, 2014) Goat Condensed tannins, % DM DM digesƟbility, % F I G U R E 3 Relationship between cow and goats for in vitro rumen digestibility in response to feeding various condensed tannin (CT)-containing browse species (Lyons, 2017 F I G U R E 4 Relationship between sheep and goats for ruminal nitrogen (N)-digestibility in response to feeding tannin-containing forages (Barry & Manley, 1984;Waghorn et al, 1987Waghorn et al, , 1990Waghorn et al, , 1998Waghorn et al, , 2002Barahona et al, 1997;Woodward and Reed, 1997;Min et al, 2002aMin et al, ,b, 2012Bengaly et al, 2007;Yisehak, Kibreab, Taye, Lourenço, & Janssens, 2016) Therefore, sheep and goats exhibited different levels of tolerance to the effects of CT (Narjisse, Elhonsali, & Olsen, 1995). Narjisse et al (1995) reported that addition of oak tannins (Quercus ilex leaves; 1 g of tannins/kg of BW) depressed ammonia levels in sheep, but not goats.…”
Section: Conden S Ed Tannin S and Protein D I G E S Tib Ilit Ymentioning
confidence: 99%
“…Feeding animals PEG next to a tannin-rich diet, has been shown to alleviate the negative effects of tannins-protein interactions in the animals gut [51,52]. Analogously, binding of CTs by PEG during protein extraction may already enhance the digestibility of the protein extracts, which would permitting their use as high-quality feed [51,52]. The costs of adding 1–1.5% PEG to the extraction process, however, would likely prohibit the practice.…”
Section: Resultsmentioning
confidence: 99%